Os rastros da língua materna - Brazão, Michelle Landim (2010)
This study is a reflection about the possibility of considering the relation between mother and foreign language, from the point of the contact between them which we called listener's strangeness. The research presented in its beginning the point of view of the Communicative Approach about a foreign language teaching. During the development of this approach the mother tongue was considered as a necessary factor. After these thoughts appeared analyses about the interference in foreign language, and one of these studies is the interlanguage hypothesis. The interlanguage, according to Selinker, is an attempt to communicate in the foreign language. However, this hypothesis alone wouldn‟t give a good answer if it was thought according to the overcome in a specific moment during the language learning. Specifically because of the learner, who is considered to be able to communicate himself and is a language pundit, shows some moments in the language which could be considered as the interference of the interlanguage. We found the support in the conception of language developed by Saussure, this conception permitted a comprehension of the language working. The language, for him, is a system which knows its own laws. The language system previews an own movement which is connect to what the linguist consider as a syntagmatic and an associative relations, relations which put in scene latent elements. The psychoanalyst theory about the slips tongue, such as it is proposed by Freud, allowed us to enquire about the existence of a law which works without the fellow‟s control. This is an unconscious law, unknown by the conscious. This way, we believed we can come closer Saussure hypothesis about the syntagmatic and associative relations - because when you evoke an idea in relation to a significant, many others are bring to the mind and put in the game - with what Freud explained as being a range of thoughts which are not conscious at the moment when somebody speaks. At this point the Moraes reflections about the mother tongue and the foreign language, by the psychoanalysis analyses, allowed us to think about the nature of the language relationship, specifically about the contact between them where we observe what we called as a listener's strangeness. Considering to Moraes that the mother tongue is the responsible to trail a path where other languages will pass, and, with Saussure‟s and Freud‟s conception, we could think about the contact between these languages are possible, when a person speaks, because of the tongue works and the unconscious. All these reflections gave to this work, elements to reflect about the moments which cause strangeness in the listener when the mother and the foreign language touch each other at a moment when anyone speaks by another point of view, different from the interlanguage. This contact of the mother and foreign language can be analyzed by the own language mechanisms and the unconscious, and they can‟t be considered overcome because they constitute the speaker.